(untitled) (Research, Society and Development, 2022)
Specific bone structures (BSDs) are critical in treating bone density, bone fractures or metastases. They can be classified as anti-resorptive or anabolic. ONJ was first associated with bisphosphonate treatment in 203, and is now recognized as an adverse effect of bisphosphonate and other BSD treatment. In this sense, this study aimed to review the literature on drug-induced osteonecrosis of the jaws, addressing diagnostic methods, as well as prevention and treatment protocols for this disease. For the construction of this article, a bibliographic survey was carried out in the databases SciVerse Scopus, Scientific Electronic Library Online (Scielo), U.S. National Library of Medicine (PUBMED) and ScienceDirect, with the help of the Mendeley reference manager. Articles Osteonecrosis between the years 2022.lars to drug-induced maxi-drug therapy, but were too necrosis for a therapy, of adverse drug consequence, but were too necrosis for a PB therapy of adverse effects. It is mainly associated with the use of more potent bisphosphonate amino acids for long periods of time. The most important antecedent event to the development of clinics is invasive dental treatment, therefore, it is important for ordinary oral health professionals to have an understanding of its causes and management. The most important aspect of the treatment starts at the time of the first preparation and must continue for the life-restoring effect of the patient due to the continued effect of the drugs on the bone.